2017
DOI: 10.1093/ons/opx246
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular Vestibular Schwannomas: Clinical Characteristics, Angiographical Classification, and Surgical Considerations

Abstract: HVS have the distinct clinical characteristics compared with those of non-HVS subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…The schwannoma on the other hand, can sometimes demonstrate intratumoral enhancing vessels reflecting microvascular proliferation and vessel hyalinization on CTA with the "salt-and-pepper appearance" on MRI (Figure 2 (a)-(c)) but a negative CTA lightbulb sign (Figures 1 (c) and 2(d)). 2,10 To our knowledge, this study is the first study of the "lightbulb sign" on CTA of the head and neck. However, in the radiology literature, lightbulb signs have been described in other entities including hepatic hemangioma 13 and adrenal pheochromocytoma, 14 as these lesions show very bright signal intensity on T2 weight sequences reminiscent of a glowing lightbulb.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The schwannoma on the other hand, can sometimes demonstrate intratumoral enhancing vessels reflecting microvascular proliferation and vessel hyalinization on CTA with the "salt-and-pepper appearance" on MRI (Figure 2 (a)-(c)) but a negative CTA lightbulb sign (Figures 1 (c) and 2(d)). 2,10 To our knowledge, this study is the first study of the "lightbulb sign" on CTA of the head and neck. However, in the radiology literature, lightbulb signs have been described in other entities including hepatic hemangioma 13 and adrenal pheochromocytoma, 14 as these lesions show very bright signal intensity on T2 weight sequences reminiscent of a glowing lightbulb.…”
Section: Discussionmentioning
confidence: 84%
“…This supports previous reports describing how schwannomas with internal vascularity ("vascularized schwannoma") on CTA can give a "salt-and-pepper appearance" on MRI mimicking paraganglioma. 9,10 Furthermore, both paraganglioma and schwannomas can demonstrate similar intense enhancement on post-gadolinium MRI (Figure 2(c)) as well as on the venous phase CECT. The previous studies using neck magnetic resonance angiography (MRA) 11,12 and dynamic contrast enhanced MRI 2 have shown the potential use in distinguishing paraganglioma from other head and neck tumors.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The blood supply of VS is an important factor affecting the di culty of surgery. Previous studies have reported on Hypervascular Vestibular Schwannomas [5][6][7][8], and several studies have shown that an abundant blood supply is signi cantly leading to an occurrence of facial impairment [9] and decrease of rate of resection [8]. The current method of preoperative assessment of the blood supply in VS is mainly by visual identi cation of the anatomical presentation of MRI and the degree of signal enhancement on T1-CE sequences.…”
Section: Introductionmentioning
confidence: 99%